A review of supplier selection methods in manufacturing industries - Tahriri, Farzad; Osman, Mohammad Rasid; Ali, Aidy; Mohd Yusuff, Rosnah (Suranaree University of Technology, 2008)
In today’s highly competitive environment, an effective supplier selection process is very important to the success of any manufacturing organization. In this context, supplier selection represents one of the most important functions to be performed by the purchasing department. Supplier selection is a multi-criterion problem which includes both qualitative and quantitative factors (criteria). A trade-off between these tangible and intangible factors is essential in selecting the best supplier. A number of models and techniques have been developed to deal with selecting and evaluating suppliers. In this paper, different selection methods concerning supplier selection are discussed and the advantages and disadvantages of selection methods, especially the Analytic Hierarchy Process (AHP), are illustrated and compared.